PENGARUH LOYALITAS, KEMAMPUAN KERJA, KEMATANGAN PEGAWAI DAN DISIPLIN KERJA TERHADAP KINERJA PEGAWAI PADA KANTOR PELAYANAN PAJAK PRATAMA MEDAN TIMUR - Harry adinata (Manajemen dan Bisnis, 2020)
The problem in this research is: How does the influence of loyalty on employee performance at the East Medan Pratama Tax Service Office. How does the effect of work ability on employee performance, How does the influence of employee maturity on employee performance, How does the influence of work discipline on employee performance, How does the influence of loyalty, work ability, employee maturity and work discipline on employee performance at the East Medan Pratama Tax Service Office. The hypothesis proposed is: Loyalty has a positive and significant effect on employee performance, work ability has a positive and significant effect on employee performance, Maturity of employees has a positive and significant effect on employee performance, Work discipline has a positive and significant effect on employee performance, Loyalty, work ability, maturity employees and work discipline have a positive and significant effect on employee performance at the East Medan Tax Service Office. The study was conducted at the East Medan Pratama Tax Office. Jalan Sukamulia No. 17-A, Medan-2015, and the study sample of 86 people.